The process of coping and self-management in the experience of recovering from chronic fatigue syndrome (CFS) - Andrews, Karen Joyce (Rhodes University, Faculty of Humanities, Department of Psychology, 2003)
A hermeneutical model of doing research is adopted to investigate the process of coping and self-management in the experience of recovering from Chronic Fatigue Syndrome (CFS). Three research participants who consider themselves as recovering or recovered from CFS were interviewed to obtain data for analysis. The findings are that once the participants cope with the uncertainty about the meaning of the onset of symptoms by defining themselves as ill in somatic terms, the participants use external social and treatment resources to cope with the onset of symptoms and being chronically ill with CFS. As a consequence of feeling stigmatised in relation to social and professional scepticism about initially being ill and subsequently, being chronically ill with CFS, the participants become uncertain about the meaning of having CFS. Coping shifts to using internal resources by adopting self-management practises. In this process, firstly, existing self-management shifts in such a way that the participants view themselves as recovering or recovered from CFS, and secondly, the participants come to the understanding that difficulties with self-management cause and maintain CFS. The findings are discussed to conclude that CFS may be a misdiagnosis of difficulties with self-management. CFS itself may not be an 'objective' disorder, but a constituent of social processes. Becoming diagnosed with CFS arises as a consequence of the search for meaning in relation to the lay and professional assumption that psychological illness does not constitute 'real' illness, operating at both the levels of popular society and the doctor-patient relationship. Difficulties with self-management rather than the diagnosis of CFS provide a more adequate understariding of the participants' illnesses.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Chronic fatigue syndrome; Chronic fatigue syndrome -- Psychological aspects